Co-relation of endometrial thickness by transvaginal sonogram with histopathology pattern in abnormal uterine bleeding: a study from South India - Mathew, Chippy Tess; Maheswari, Uma; Shanmugam, Karthikeyan (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2020)
Background: Under normal circumstances, a woman’s uterus sheds a limited amount of blood during each menstrual period (around 80 ml). Bleeding that occurs erratically or excessive menstrual bleeding is called abnormal uterine bleeding (AUB). The causes of AUB are many and varied. Initial investigations include transvaginal ultrasound and histopathologic assessment of the endometrium. Objective of this study was to evaluation of endometrial thickness with trans-vaginal ultrasound and its correlation with histopathology by dilatation and curettage in abnormal uterine bleeding. To determine the efficacy of transvaginal ultrasound in evaluating the endometrial thickness. To correlate the endometrial thickness by transvaginal ultrasound with endometrial histopathology in women with AUB. Methods: It is a retrospective observational study. All reproductive and perimenopausal age group women who underwent dilatation and curettage for abnormal uterine bleeding during the period June 2014-June 2016 was taken and analyzed and correlated with their endometrial thickness measured with Transvaginal ultrasound. Results: Around 478 patients who underwent endometrial sampling over a period of two years were analyzed. Maximum number of patients were in the fourth decade and the overweight category 36.6%. Proliferative endometrium was the most common histopathologic picture (44.76%). Detection of precancerous lesions were-5.87% and endometrial cancer was 1.05%. Conclusions: An ET of 8 mm and above gave 100% sensitivity and negative predictive value for precancerous and cancerous lesions.